An investigation of the quality of FET Physical Sciences formative assessments from selected schools in South Africa - Molise, Thabang Daniel (My University, 2022)
Formative assessments are increasingly considered as an integral part of the teaching and learning process, because of their perceived ability to improve learners’ academic achievement. Formative assessments are used to monitor learners’ progress and are envisaged to promote the teaching and learning process. Because of the perceived effectiveness of formative assessments in improving the teaching and learning process, researchers have advocated for their frequent use in classrooms. If formative assessments are as important as perceived by stakeholders, then their quality should be ascertained to ensure that they achieve their intended goal. Unfortunately, most institutions tasked with the responsibility of monitoring the development and implementations of formative assessments in schools tend to focus mainly on determining learner performance on the assessments, and rarely evaluate their quality. In South Africa, formative assessments, commonly referred to as School Based Assessments (SBAs) are designed by both educators and the department of education and are administered by educators in schools. Assessment records in South Africa indicate that the performance of Further Education and Training (FET) Physical sciences learners in SBAs has been unsatisfactory since the adoption of the Curriculum and Assessment Policy Statement (CAPS). The quality of these assessments could partly account for the observed poor learner performance as they might not be measuring what they are intended to measure. This study used a qualitative multiple case study design to investigate the quality of Physical sciences formative assessments in selected South African schools, and the factors that influence educators’ choices of formative assessment items. The critical Formative Assessments (FA) components framework (Herman, Osmundson & Silver, 2010) guided the study. The sample comprised of nine FET Physical sciences formative assessment past papers, administered to Grades 10 to 12 learners in 2019 and three Physical sciences educators. Data were collected using both document analysis and semi-structured interviews and the findings show that most of the analysed formative assessments are of low quality, and that educators rarely considered assessment quality indicators when designing formative assessments. We therefore recommend the training of Physical sciences educators in designing quality formative assessments.
A research report presented in partial fulfilment of the requirement for the degree of Masters in Education to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022